Dipole and quadrupole polarizabilities and shielding factors of beryllium from exponentially correlated Gaussian functions - Komasa, Jacek (American Physical Society, 2001)
Dynamic dipole and quadrupole polarizabilities as well as shielding factors of the beryllium atom in the ground state were computed at real frequencies by using the variation-perturbation method. The zeroth- and the first-order wave functions were expanded in many-electron basis of exponentially correlated Gaussian functions. The 1600-term expansion of the unperturbed wave function yielded the ground-state energy accurate to 1 cm-1. The first-order wave functions were expanded in very large bases (4800 and 4400 terms). The nonlinear parameters of the first-order correction functions were optimized with respect to both the static and dynamic polarizabilities, and with respect to the excited-state energies. The procedure employed ensures a high accuracy of determination of dynamic properties in a wide range of frequencies and correct positions of the transition poles. Test calculations, performed on He and Li, confirmed the ability of this method to obtain the atomic properties with very high accuracy. The final values of the static properties of Be were 37.755 e2a02EH-1 and 300.96 e2a04EH-1 for the dipole and quadrupole polarizabilities, respectively, and 1.4769 for the quadrupole shielding factor. The convergence of the atomic properties with the size of the expansion of both the zeroth- and first-order functions was checked. Thanks to very high accuracy of the unperturbed wave function and the efficient method of construction of the first-order wave functions, the dynamic polarizability results presented in this work are of benchmark quality. As a by-product of this project, a set of the most accurate upper bounds to the energies of 1P and 1D states of Be was obtained.
Keywords: dynamic polarizability; shielding factor; beryllium atom; variation-perturbation method; exponentially correlated Gaussian functions; cauchy moments; refractive index; verdet constant